Improving the Quality of Palm Oil NPK Fertilizer Products at PT.XYZ Using Statistical Process Control Methods and Taguchi Experiment - Hariono Hariono; Mokh. Suef (Institut Teknologi Sepuluh Nopember, 2020)
Quality palm oil NPK fertilizer products are fertilizer products that meet the quality requirements specified in SNI Standard 2801: 2010 and SIRIM Standards. This research was conducted with the aim to improve the quality of oil palm NPK fertilizer products at PT. XYZ. To maintain the stability of nutrients, the production process must be strictly considered with the aim of minimizing product variations. To achieve these objectives the production process control system is designed using Statistical Process Control. Then a process is designed to produce a robust product using the Taguchi experiment. Taguchi experiment obtained the results of the optimization of the process parameter level settings in combination as follows: raw material intake 27 mt / hour; water usage 1100 m3 / hour; gas usage 100 MMBtu; material temperature granulator 52°C; dryer material temperature 52°C; cooler material temperature of 44°C; finish product temperature 39°C; process environment temperature of 31°C. From the results of ANOVA for each nutrient showed that the highest levels of nutrient N were obtained from the finish product temperature 38°C; the highest P2O5 nutrient content is obtained from the variable water usage of 1000 m3 / hour; the highest K2O nutrient content is obtained from the variable water usage of 1100 m3 / hour; the highest MgO nutrient content is obtained from the variable gas usage of 90 MMBtu; The highest levels of B2O3 nutrients are obtained from the variable water usage of 1100 m3/hour and the best physical size of the granules is obtained from the variable cooler material temperature of 42oC. The results of this study can reduce as much as possible complaints from customers because the product meets the quality standard specifications required.